Antimicrobial Resistance in Western Australian Hospitals: Impact of Antimicrobial and Non-antimicrobial Drug Prescribing. - Abbas, Zahraa Mahdi (Curtin University, 2024)
This thesis consisted of two studies that explored different factors contributing to the growing antimicrobial resistance threat. In the first study, appropriateness of antibiotic prescribing at a large hospital in Western Australia was investigated. The second study investigated associations between the use non-antibiotic agents that have antimicrobial properties, specifically statins, and nasal Staphylococcus aureus colonisation. This research highlighted the need for multifaceted approaches that include judicious use of all medications to prevent antimicrobial resistance.